Left Ventricular Filling Pressures Contribute to Exercise Limitation in Patients with Continuous Flow Left Ventricular Assist Devices. Issue 3 (March 2020) - Koshy, Aaron; Bouzas-Cruz, Noelia; Okwose, Nduka C.; Fernandez, Oscar Gonzalez; Green, Thomas; Woods, Andrew; Robinson-Smith, Nicola; Tovey, Sian; McDiarmid, Adam; Parry, Gareth; Schueler, Stephan; Jakovljevic, Djordje G.; et al.
Abstract : We sought to determine hemodynamic mechanisms of exercise intolerance in a group of patients with the HeartWare ventricular assist device (VAD) compared to a group of heart failure patients. Twenty VAD and 22 heart failure patients underwent symptom-limited active straight leg raising exercise during right heart catheterization with thermodilution (TD), and upright cycling cardiopulmonary stress testing with cardiac output measurement by inert gas rebreathing (IGR) method. The TD and IGR exercise cardiac indexes were higher in VAD compared with heart failure group (both P < 0.05), although there was only a borderline increase in peak exercise oxygen consumption (VO2 ) ( P = 0.06). Baseline and exercise right heart catheterization pressures were not significantly different between the two groups. The only significant independent predictors of peak VO2 in the heart failure group were exercise heart rate and cardiac index (both P < 0.05). In contrast, for the VAD group only, resting pulmonary arterial wedge and pulmonary arterial mean pressures were independently related to peak VO2 (both P < 0.05). Thus, in heart failure, exercise cardiac index is an important limitation to exercise capacity, and VADs increase exercise cardiac index. However, in VAD patients, this only produces limited benefits as increased pulmonary and pulmonary wedge pressures limit increases in exercise capacity. Abstract : Supplemental Digital Content is available in the text.